How can Proactive Behavior be Encouraged in Hospitals of Bangladesh? A Three-Time Lags Study - Asadullah, ABM; Sadia, Raihana; Abdullah, ABM (Asian Business Review, 2022)
Proactive behavior helps an individual in improving the work setting. Based on the JD-R theory and Borden and build approach, this research proposes and tests a serial mediation relating the strengths used with proactive behavior sequentially through work authenticity and self-resilience. A sample of 256 employees of hospitals in Bangladesh was approached in three-time lags. The Process Marco of Preacher and Hayes was applied to investigate the proposed hypotheses. The indirect effects of the proposed hypotheses were measured by applying the bootstrap procedure. The results showed that work authenticity mediated the relation among strengths use and self-resilience, self-resilience mediated the association between work-authenticity and proactive behavior, and work-authenticity and self-resilience sequentially judged the connection between forces use and assertive behavior. Through an investigation of self-resilience, the outcomes provide proof supporting combining the JD-R and Borden and building theories in the research stream. Future research should add potential moderators that can impact the paths and apply longitudinal design to permit solid causal relationships. Considering the role of work authenticity and self-resilience in positive psychology, organizations must stimulate employees to become more authentic and self-resilient on the job. This increases proactive behavior and leads to the success of an organization.
Keywords: Organizational Behavior; Work Authenticity; Strengths Use; Self-Resilience; Proactive Behavior; Serial Mediation